Van Neck-Odelberg disease in a 8-year-old children: a rare case report - Ceri, Lorenzo; Sperati, Gianluca (Acta Biomedica Atenei Parmensis, 2020)
Introduction. osteochondrosis of ischiopubic synchondrosis (IPS)” also known as van Neck- Odelberg disease (VNOD), is a syndrome characterized by an atypical ossification pattern of the ischiopubic joint. Because of its non-unequivocal radiological features, which can mimic stress fracture, infection disease, neoplasm or post-traumatic osteolysis, these different diagnoses need to be rule out. Case presentation. We present an 8-year-old, obese, right limb dominant child that complained only slight groin pain and a limp on left side for more than 20 days. Neither the patient nor his parents recall any trauma. On clinical examination, no swollen lymph nodes were noticeable. After digital pressure, the patients reported a dragging feeling in the left groin, radiating into the medial left thigh and limitation of Range of Motion (ROM) were present. Thus, a plain X-ray and MRI were performed, revealing VNOD on left ischiopubic ramus. The boy was then treated with regular NSAID and pain adapted full weight bearing and a clinical check at 30 and 60 days was performed. At the last visit, the symptoms were completely disappeared and the patient totally recovered left hip function. Conclusion. Diagnosis of VNOD is challenging and clinical presentation is not pathognomonic. So, other benign or severe conditions need to be rule out. Once this disease is diagnosed, the prognosis is generally favourable.